Safeguarding Fishermen's Livelihoods: A Human Rights Approach Against Coastal Reclamation - Palilingan, Toar Neman; Pinori, Josepus Julie; Lengkong, Natalia Lana; Yunus, Ahsan; Setiabudhi, Donna Okthalia (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Coastal reclamation has become a controversial issue with significant impacts on the lives of local fishermen. Reclamation activities aimed at regional and economic development often neglect the rights of traditional fishermen who depend on the sea for their livelihoods, leading to conflicts between development interests and the protection of human rights, particularly the rights of local fishermen.Purposes of the Research: This study aims to analyze the legal protection of fishermen in the context of reclamation in North Sulawesi, focusing on a human rights perspective.Methods of the Research: The research employs a normative juridical approach, examining relevant legislation related to reclamation and fishermen's rights, as well as analyzing the implementation of laws in practice.Results of the Research: The findings reveal that reclamation in North Sulawesi presents two conflicting sides. On one hand, it offers significant economic benefits to the state, but on the other hand, it poses a risk of human rights violations, particularly for coastal fishermen. The negative impacts of reclamation are evident in the decline in fishermen's income and the increase in living costs since the project was implemented. Legal protection of fishermen's human rights must be enforced through strict sanctions, including substantial fines, against parties who fail to fulfill their obligations to the fishermen.